Draft Annual Plan (2011-12) Proposals Government of Manipur - Planning Commission (Planning Commission, 2010)
Manipur is a border land-locked state and it does not have any waterways and effective railway transport system (despite a railhead at Jiri bam in the south western border). The State is connected by air with Delhi and Calcutta. However, roads constitute the most important transport system. Three National Highways NH-39, NH-53 and NH-150 connect the State with the rest of the country. NH-39 links Imphal with the railway head of Dimapur in Nagaland at a distance of 215 kms to the north, NH-150 with Mizoram and Nagaland, and NH- 53 with Silchar in Assam towards the south west.
Government of Manipur, Planning Department